2020
DOI: 10.1001/jamanetworkopen.2020.27577
|View full text |Cite
|
Sign up to set email alerts
|

Association of Number of Doses With Hepatitis B Vaccine Series Completion in US Adults

Abstract: IMPORTANCE Receipt of hepatitis B virus vaccine is important to prevent infection. However, adherence to the hepatitis B vaccine series among adults at risk of infection has been low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…It is also the first to use a geographically diverse administrative claims database to examine socioeconomic factors associated with both adherence and completion. In contrast, existing studies have tended to be restricted to higher risk populations [ 14 , 15 , 24 , 25 ] or localized geographic areas [ 16 ]. A recent study using self-reported NHIS survey data found poor coverage rates for hepatitis vaccines and although that study assessed sociodemographic correlates, information on adherence was not provided [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also the first to use a geographically diverse administrative claims database to examine socioeconomic factors associated with both adherence and completion. In contrast, existing studies have tended to be restricted to higher risk populations [ 14 , 15 , 24 , 25 ] or localized geographic areas [ 16 ]. A recent study using self-reported NHIS survey data found poor coverage rates for hepatitis vaccines and although that study assessed sociodemographic correlates, information on adherence was not provided [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm and extend the body of evidence from previous real-world administrative claims studies which have shown that low completion rates for hepatitis vaccines are associated with risk factors such as age, race, income level, region, and specific comorbidities [ 11 , 12 , 24 , 26 ]. Bruxvoort et al recently reported higher completion rates for 2-dose or 3-dose Hepatitis B vaccines among those who were older, female, white, Asian or Pacific Islander, living in a census block with higher median income or with >75% of individuals with high school education or higher [ 16 ]. However, their analysis utilized data from Kaiser Permanente, an integrated healthcare delivery network in Southern California, whereas our study used a large claims database that is more representative of the entire US [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the multivariable models adjusting for these factors and recruitment location, we similarly found greater receipt of HAV vaccination among those with longer confinement. This finding indicates that jails, prisons, and detention centers may be missed opportunity locations to reach and deliver recommended adult vaccines [40,69].…”
Section: Discussionmentioning
confidence: 99%
“…Noncompletion of a 3-dose vaccine over 6 months is frequent, 1,2 and a recent study found that a 2-dose vaccine has better adherence than a 3-dose vaccine among US adults. 3 New HBV infections in the United States are the highest among those aged 30 to 49 years, 4 with 33.2% of those aged 25 to 39 years, 32.0% of those aged 45 to 54 years, and 27.6% of those aged 55 years and older in 2016. 5 Health care workers, the military, and travelers to endemic regions are most in need of an HBV vaccine that ensures rapid seroprotection.…”
Section: Introductionmentioning
confidence: 99%